The harmonization of business and employees' personal goals - Nosak Timea; Zubanov Violeta (University Educons, Faculty of Sports and Tourism, Novi Sad, 2013)
The study presented in the paper deals with the problem of harmonizing business and employees' personal goals, as well as issues of organizational support to employees with the aim of achieving life balance. The research is based on how organization affects achieving life balance of their employees and how employees manage to balance between business and personal obligations. The study focuses on the elements that relate to a healthy lifestyle and a healthy diet. The key part of the research is related to follow up on employees' obligations outside of working hours and the quality time spent on resting and relaxing. The organizational support elements are examined, as well as written evidence of Work-Life Balance policies, support from organization's culture, support from superiors and the perceived work satisfaction.